The Rare Association of Imperforate Anus with Neurogenic Bladder Dysfunction and Later Development of Retrograde Ejaculation: An Educational Article and expert Opinion - Aamir Jalal Al-Mosawi (International Journal of Pharmaceutical & Biological Archive, 2024)
Background: Retrograde ejaculation, a condition where semen is redirected into the bladder rather than being expelled through the urethra during orgasm, can be caused by various factors including congenital abnormalities and surgical interventions. Effective management is crucial for improving patient outcomes and addressing associated symptoms. Patients and Methods: This paper explores a rare case of retrograde ejaculation associated with an imperforate anus and neurogenic bladder dysfunction. It also reviews various evidence-based treatments for retrograde ejaculation and evaluates the role of alfuzosin in managing related symptoms. The paper underscores the value of oral alfuzosin in managing this condition and to review the pharmacological treatments available for retrograde ejaculation. Results: A 17-year-old male with a history of imperforate anus and bilateral hydroureteronephrosis underwent treatment with oral alfuzosin, an alpha1-adrenergic blocker. The patient experienced significant improvements in hydroureteronephrosis following 1 year of treatment with oral alfuzosin. Initial treatment involved a daily dose of 2.5 mg, which was increased to 5 mg after 1 month, and subsequently adjusted to 10 mg daily. The treatment led to reduced hydroureteronephrosis and preserved renal function. Conclusion: This case supports the use of long-term oral alfuzosin as a non-invasive therapeutic option for neurogenic bladder dysfunction and retrograde ejaculation. Evidence from the literature indicates that a range of medical therapies can offer significant benefits for patients with retrograde ejaculation, underscoring the importance of individualized treatment strategies.